Infant Feeding Information, Attitudes and Practices: a Longitudinal Survey in Central Nepal - Karkee, Rajendra; Lee, Andy; Khanal, Vishnu; Binns, Colin (BioMed Central, 2014)
Background: Infant feeding is governed by environmental as well as cultural factors. Breastfeeding knowledge and attitudes are known to be associated with breastfeeding duration. This study investigated breastfeeding information, attitudes and supplementary feeding in the central hills district of Nepal.Methods: A community-based prospective cohort study of 701 pregnant women was conducted. Information on breastfeeding attitudes, feeding practices and supplementary feeding was sought from the cohort at 4 weeks, 12 weeks and 22 weeks postpartum through repeated interviews using validated questionnaires.Results: Average duration of intended breastfeeding was 28 months (SD 7.9) and average target time to introduce solid foods was 6.1 months (SD 1.2). About 80% of women reported their husband, mother/mother-in-law preferred breastfeeding. Eleven percent of the cohort said that breastfeeding was not enjoyable. At 12 weeks and 22 weeks after birth, about a quarter (24.8%) and half (52.8%) of the infants were introduced cow/buffalo milk, respectively, while only 6.3% and 13.4% of them were given infant formula. Overall, any breastfeeding rate remained high at over 98% throughout the follow up period.Conclusions: Breastfeeding attitudes were encouraging in this population. Breastfeeding was almost universal. Use of infant formula was quite low, whereas cow or buffalo milk appeared to be popular supplementary foods.